Complex to simple: In vitro exposure of particulate matter simulated at the air-liquid interface discloses the health impacts of major air pollutants. (May 2019) - Wang, Ruixia; Chen, Rui; Wang, Youfeng; Chen, Lan; Qiao, Jiyan; Bai, Ru; Ge, Guanglu; Qin, Guohua; Chen, Chunying
Abstract: Particulate matter (PM) exposure poses many adverse effects on human health. However, it is challenging to clearly differentiate between the contributions of individual pollutants on toxicity from complex mixtures of ambient air pollutants. The aim of this study is to generate aerosols constituted by silica nanoparticles (NPs) and bisulfate to serve as simulators of particle-associated high-sulfur air pollution. Then, the health impacts of sulfur dioxide were evaluated at the cellular level using an air-liquid interface (ALI) exposure chamber. BEAS-2B cells were exposed to either nano-silica or bisulfite aerosol individually or bisulfate-coated silica (SiO2 -NH2 @HSO3 ) for 3 h using the ALI. The cellular toxicities were carefully compared based on the exposure dosages. The ALI exposure of SiO2 NPs alone did not produce any apparent cytotoxicity in cells, but the aerosol exposure of SiO2 -NH2 @HSO3 significantly decreased the cell viability and enhanced the production of cellular reactive oxygen species in a dose-dependent manner. Consequently, the excessive oxidative stress resulted in mitochondrial damage as well as cellular apoptosis. ALI exposure can possibly reflect the realistic physiological exposure condition of the human respiratory system. As a derivative of the sulfur dioxide component of air pollution, sulfate exacerbates the toxic effects of inhalable PMs. This result may be due to the large surface area of the nanoparticles, with the possibility of carrying more sulfite to the target cells during aerosol exposure. The sulfate levels offer a meaningful complement to the present PM2.5 index of air pollution for achieving better human health protection. Graphical abstract: Image 1 Highlights: Air-liquid interface exposure was used to evaluate the cytotoxicity of pollutants. The SiO2 -NH2 nanoparticles with carrying HSO3 − simulate atmospheric pollutants. The ratio of HSO3 − bounded on the silica represents for different pollution level of sulfate in actual environment. Sulfate exacerbates the toxic effects of the inhalable particular matters. SiO2 -NH2 @HSO3 induces apoptosis by activating mitochondrial stress pathway.